CALCULATION OF REINFORCED CONCRETE SLAB STRUCTURE UNPROTECTED FROM SUNLIGHT IN NATURAL CLIMATE IN LIRA PK PROGRAM - Abdurahmonov Abdukholiq, son of Abdukhodi; Abdukhamidov Golibjon, son of Gayratali (Journals Park Publishing, 2023)
The article provides information about the influence of natural climatic conditions on the design of buildings and structures. The author emphasizes that design and construction, taking into account the local climate conditions, based on the characteristics and functional requirements of the building or structure being designed, allows to find an effective solution. It is necessary to take into account various factors when designing the architectural construction solutions of the project object: i.e. air temperature, solar radiation, humidity, wind speed, precipitation. It is desirable to find a solution using modern technical means in the construction of new architectural forms, original planning projects.
Keywords: Natural climatic conditions, creation of a calculation scheme, research analysis.